2019
DOI: 10.18542/cepec.v3i1-6.6838
|View full text |Cite
|
Sign up to set email alerts
|

O Arranjo Produtivo da Mandioca e Análise da Sazonalidade de Preços da Farinha no estado do Pará

Abstract: Este trabalho teve como objetivo analisar a organização do arranjo produtivo local (APL) da mandioca no estado do Pará, assim como a sazonalidade dos preços da farinha no atacado. A metodologia empregada foi através do levantamento bibliográfico para o Arranjo e de dados secundários acerca da produção da mandioca e preços no atacado para o cálculo da sazonalidade. O resultado mostrou que inexiste arranjo produtivo da mandioca no Pará, dado a ausência de políticas públicas para este APL, de modo a evoluir e se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…(1.21) was similar to that described bySilva et al (2014) (1.22) when analyzing the accumulation of dry matter and micronutrients and cassava consortium with banana tree.The value obtained for the total leaf area (6.25 m²) (Table1), is well below that observed byCoelho Filho et al (2017) when studying the growth and productivity of the consortium cassava and caupi beans, found a maximum leaf area value of 3.10 m². It can be inferred from this result that factors such as spacing, time of harvest, soil type, may have influenced the achievement of greater leaf area in this study.…”
supporting
confidence: 83%
“…(1.21) was similar to that described bySilva et al (2014) (1.22) when analyzing the accumulation of dry matter and micronutrients and cassava consortium with banana tree.The value obtained for the total leaf area (6.25 m²) (Table1), is well below that observed byCoelho Filho et al (2017) when studying the growth and productivity of the consortium cassava and caupi beans, found a maximum leaf area value of 3.10 m². It can be inferred from this result that factors such as spacing, time of harvest, soil type, may have influenced the achievement of greater leaf area in this study.…”
supporting
confidence: 83%
“…Although the use of cassava is considered versatile, it is observed that much of the production of Pará is focused on the manufacture of flour, which always occurs in a handmade way and for subsistence, because it is considered one of the items that are part of the food of paraenses. In addition, it is observed that the profile of cassava producers in Pará is composed of a large number of small farmers, as well as the presence of small agroindustries of tapioca flour and cassava flour, spread basically throughout the territory of Pará (Silva et al, 2014).…”
Section: State Productionmentioning
confidence: 99%
“…Chlorine-based chemical disinfection is the most widely used in the food industry as they are good antibacterials and, if used in the proper concentrations the product leaves no unpleasant flavors or odors. Among the chlorine compounds, the most common are calcium and sodium hypochlorites (Silva et al, 2014).…”
Section: Minimum Cassava Processingmentioning
confidence: 99%